1994
DOI: 10.1136/oem.51.4.239
|View full text |Cite
|
Sign up to set email alerts
|

Findings from high resolution computed tomography of the lung and pleura of symptom free workers exposed to amosite who had normal chest radiographs and pulmonary function tests.

Abstract: The lungs of 50 symptom free workers exposed to amosite and with normal pulmonary function tests were examined by high resolution computed tomography (HRCT). Twenty five had normal standard chest radiographs whereas the other 25 had radiographs interpreted as near normal (International Labour Office profusion score <01 or suspected pleural plaques). In 13 of the workers the results of HRCT were negative; in 22 pleural plaques were found, in five there was only parenchymal involvement, and 10 had both pleural a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 14 publications
0
11
2
Order By: Relevance
“…Previously radiographic and CT studies reported that unilateral pleural plaques were not infrequent [38,39]. In contrast to these studies, we did not observe any side predominance, but it should be remembered that workers with bilateral calcified pleural plaques visible on the chest radiograph were not referred for CT scans and, therefore, a selection bias existed.…”
Section: Unilateral Versus Bilateralcontrasting
confidence: 54%
See 1 more Smart Citation
“…Previously radiographic and CT studies reported that unilateral pleural plaques were not infrequent [38,39]. In contrast to these studies, we did not observe any side predominance, but it should be remembered that workers with bilateral calcified pleural plaques visible on the chest radiograph were not referred for CT scans and, therefore, a selection bias existed.…”
Section: Unilateral Versus Bilateralcontrasting
confidence: 54%
“…In contrast to these studies, we did not observe any side predominance, but it should be remembered that workers with bilateral calcified pleural plaques visible on the chest radiograph were not referred for CT scans and, therefore, a selection bias existed. As far as we know, the leftsided predominance for the presence as well as for the extent of asbestos-related pleural disease has been reported in radiographic studies [39,40], but the only CT study reporting unilateral plaques did not investigate their side predominance [38]. In contrast to pleural plaques, diffuse pleural thickening, parenchymal bands and rounded atelectasis were bilateral in only a minority of the subjects included in the present study.…”
Section: Unilateral Versus Bilateralcontrasting
confidence: 45%
“…Whereas established asbestosis has been reported to be associated with respiratory functional impairment mainly of the restrictive type (3,12,22), several authors have described the presence of interstitial abnormalities on HRCT, consistent with early-stage asbestosis, in asymptomatic participants without any functional or Xray abnormalities (7,9). These findings suggest that early-stage HRCT abnormalities might precede functional impairment.…”
Section: Discussionmentioning
confidence: 97%
“…Systematic use of HRCT for cohorts of people who have been exposed to asbestos revealed interstitial abnormalities consistent with asbestosis in a sizeable fraction of the asymptomatic persons whose posteroanterior chest X-rays (7)(8)(9) or pulmonary function (7,9) were considered normal. As a result, systematic HRCT scanning with a 6-year periodicity was recommended recently in France for the diagnosis of asbestosis for people who are over 50 years of age and have had high occupational exposure to asbestos (10).…”
mentioning
confidence: 99%
“…MRI is much less sensitive than CT (Evans & Gleeson, 2004). Most frequently, pleural plaques are diagnosed using radiographic methods including CXR or CT. Use of CT scans increases both sensitivity and specificity compared to standard CXR (Al Jarad et al, 1991;Neri et al, 1994;O'Reilley et al, 2007;Roach et al, 2002) but results from these two methods are correlated (Suganuma et al, 2001). High-resolution computed tomography (HRCT) is superior to CT (Lynch et al, 1989).…”
Section: Introductionmentioning
confidence: 99%